(untitled) (Zaporizhzhia Historical Review, 2021)
In the article on the basis of the complex analysis of set of written sources about a history of Carpats Black Sea Region region in ХІІ - first half ХІІІ senturies is described the extraordinary complexity of ethnopolitical conditions in these territories. Simultaneously is shown the intensive penetration of the slavic Ukrainian population in Territories between the rivers of a Prut and Dniest, and also for Danube, where subsequently was formed ìThe Bottom part of Galichî (ìGalitskoe Ponizëeî).